Pengaruh Quality Of Work Life, Self Determination, DanJob Performance Terhadap Work Engagement Karyawan(Studi Pada Karyawan Pt. Pamor Spinning Mill's Di Karanganyar) - Sri Wulandari KN, Alifa, Ir. Irmawati, S.E., M.M (2017)
This Research aims to identify and empirically examine (1) the effect of quality of work life on the work engagement. (2) the effect of self determination on work engagement. (3) the impact of job performance on work engagement. (4) the effect of Quality of Worklife, Self Determintion, and Job Performance simultaneously on the work engagement. Variables that used in this study were Quality of Worklife, Self Determintion, Job Performanceas independent variables andwork engagementas adependent variable. The sample of this research was 100 employees of PT. Pamor Sinning Mill'sas respondents by random sampling techniques. Methods of data collection by using questionnaires. Data analysis techniques is multiple regression analysis, F test, andt test. The t test showed that all independents variable has partial effect on the dependent variable, while Ftest analysis data finds that there are 2 simultaneously effect of variables quality of work life, self determination, and job performance on the work Engagement.